The Superoanterior Fasciculus (SAF): A Novel White Matter Pathway in the Human Brain? - David, Szabolcs; Heemskerk, Anneriet M.; Corrivetti, Francesco; Thiebaut de Schotten, Michel; Sarubbo, Silvio; Corsini, Francesco; De Benedictis, Alessandro; Petit, Laurent; Viergever, Max A.; Jones, Derek K.; Mandonnet, Emmanuel; Axer, Hubertus; et al. (Frontiers in Neuroanatomy, 2019)
Fiber tractography (FT) using diffusion MRI (dMRI) is widely used for investigating microstructural properties of white matter (WM) fiber-bundles and for mapping structural connections of the human brain. While studying the architectural configuration of the brain’s circuitry with FT is not without controversy, recent progress in acquisition, processing, modeling, analysis, and visualization of dMRI data pushes forward the reliability in reconstructing WM pathways. Despite being aware of the well-known pitfalls in analyzing dMRI data and several other limitations of FT discussed in recent literature, we present the superoanterior fasciculus (SAF), a novel bilateral fiber tract in the frontal region of the human brain that – to the best of our knowledge – has not been documented. The SAF has a similar shape to the anterior part of the cingulum bundle, but it is located more frontally. To minimize the possibility that these FT findings are based on acquisition or processing artifacts, different dMRI data sets and processing pipelines have been used to describe the SAF. Furthermore, we evaluated the configuration of the SAF with complementary methods, such as polarized light imaging and human brain dissections. The FT results of the SAF demonstrate a long pathway, consistent across individuals, while the human dissections indicate fiber pathways connecting the postero-dorsal with the antero-dorsal cortices of the frontal lobe.